Incidence of Venous Thromboembolism in cancer patients treated with Cisplatin based chemotherapy — a cohort study. Issue 1 (December 2017) - Zahir, Muhammad; Shaikh, Quratulain; Shabbir-Moosajee, Munira; Jabbar, Adnan
Abstract Background Cancer related thrombosis not only increases morbidity and mortality but also poses a significant financial burden on health care system. Risk of venous thromboembolism (VTE) in these patients substantially increases with the addition of chemotherapy. Lately, cisplatin has been implicated as an independent factor. There is little data estimating the risk of venous thromboembolism in patients receiving cisplatin based chemotherapy when compared to other chemotherapeutic agents. Methods Patients who had received chemotherapy between November 2010 and October 2012 were retrospectively identified from a single institute cancer registry. 200 patients who had received cisplatin based chemotherapy were identified as the exposed group while 200 patients who had received non-Cisplatin based regimens were identified as the non-exposed group. Patients were followed for development of VTE throughout the entire duration of therapy and one month thereafter. Cox proportional hazard model was used to compute relative risks with 95% confidence intervals. Results The baseline characteristics were similar in the two groups. Mean age for the entire cohort was 55.4 ± 10.7 years and male to female ratio was almost 1:1. On univariate analysis, cisplatin based chemotherapy, presence of central venous catheter, female gender, poor performance status, high risk stratification according to the Khorana model and use of granulocyte colony stimulating factor were all significantly associated with the development of VTE. The crude relative risk for the incidence of VTE in cisplatin group was 2.8 (95% CI, 1.4 – 4.2) times compared to the non-Cisplatin group. When the relative risk was adjusted for the above variables in multivariable analysis, it increased to 3.3 (95% CI, 1.6 – 6.8) compared to the control group. Conclusion A high incidence of VTE in patients receiving cisplatin based chemotherapy was demonstrated in this study. Prospective studies are warranted to establish this observation with certainty and to explore the possible use of thromboprophylaxis in patients receiving cisplatin based chemotherapeutic regimens.